2021
DOI: 10.1002/cncy.22537
|View full text |Cite
|
Sign up to set email alerts
|

RAS mutation and associated risk of malignancy in the thyroid gland: An FNA study with cytology‐histology correlation

Abstract: Background Activating point mutations of the RAS gene (NRAS, HRAS, and KRAS) can be seen in benign and malignant thyroid tumors; among these, NRAS mutations are more commonly seen. This study was conducted to evaluate the thyroid risk of malignancy (ROM) associated with RAS mutations in thyroid fine‐needle aspiration (FNA) at the authors' institution. Methods The authors searched their electronic database system between January 2015 and May 2021 for thyroid FNA cases with any type of RAS mutation. Molecular al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…26,27 RAS gene mutations in the AUS category have been associated with a lower ROM (17%) than cases with a cytologic diagnosis of suspicious for a follicular neoplasm, which has a higher ROM (38%). 28 Isolated HRAS mutations appear to have a higher ROM compared with NRAS and KRAS mutations. 28 RAS-like mutations, including BRAF K601E, THADA::IGF2BP3, and PAX8::PPARγ, were mainly found in the FC-A subcategory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 RAS gene mutations in the AUS category have been associated with a lower ROM (17%) than cases with a cytologic diagnosis of suspicious for a follicular neoplasm, which has a higher ROM (38%). 28 Isolated HRAS mutations appear to have a higher ROM compared with NRAS and KRAS mutations. 28 RAS-like mutations, including BRAF K601E, THADA::IGF2BP3, and PAX8::PPARγ, were mainly found in the FC-A subcategory.…”
Section: Discussionmentioning
confidence: 99%
“…28 Isolated HRAS mutations appear to have a higher ROM compared with NRAS and KRAS mutations. 28 RAS-like mutations, including BRAF K601E, THADA::IGF2BP3, and PAX8::PPARγ, were mainly found in the FC-A subcategory. BRAF K601E is reported to be the second most common BRAF mutation found in thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Nodular hyperplasia (NH) morphologically mimics FA, and the two can be difficult to differentiate. However, a growing number of reports have documented RAS mutations in NH [ 11 , 12 , 13 ]. A recent publication implicated additional alterations in the expressions of genes involved in cell cycle, apoptosis, and PI3K pathway, and stromal factors to lead to a stepwise progression of NH to malignancy [ 12 ].…”
Section: Molecular Landscape Of Follicular Cell-derived Thyroid Cancermentioning
confidence: 99%
“…14 Gilani et al explored the risk of malignancy of KRAS, HRAS, and NRAS alterations identified on thyroid FNAs and in their representative figures, cases demonstrated either architectural atypia in a microfollicular or crowded pattern with occasionally some nuclear atypia. 17 Similarly, in their cohort of AUS thyroid lesions, Glass et al identified 15 cases with RAS mutations that were varied with cases harboring either architectural atypia, cytologic atypia or Hurthle cell change. 14 Overall, when evaluating thyroid FNAs from RAS-like lesions, it would be difficult to ascribe a particular genetic driver primarily based on cytomorphology, due to significant overlap among RAS-like tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Glass et al mentioned previously, their cohort included two cases harboring a PAX8::PPARgamma and four cases with PTEN alterations with all cases showing only architectural atypia 14 . Gilani et al explored the risk of malignancy of KRAS , HRAS , and NRAS alterations identified on thyroid FNAs and in their representative figures, cases demonstrated either architectural atypia in a microfollicular or crowded pattern with occasionally some nuclear atypia 17 . Similarly, in their cohort of AUS thyroid lesions, Glass et al identified 15 cases with RAS mutations that were varied with cases harboring either architectural atypia, cytologic atypia or Hurthle cell change 14 …”
Section: Discussionmentioning
confidence: 99%